Basic Knowledge and Criteria for Truthfulness from West and Islamic Perspectives - Ilham Adiansyah Harahap; Ahmad Rifai; Hendra Alsa Fahmi; Salminawati Salminawati (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The aim of this research is to find out what knowledge is, what is the source and basis of knowledge? The results of this research Truth is a condition or thing that is in accordance with reality or actual reality. For example, the truth of this news is still in doubt, and we must be firm in defending truth and justice. According to Abbas Hamami, the word “truth” can be used as a noun which can be something concrete or abstract. When someone states a “truth,” they are referring to a proposition that is true. Theories of truth include: The first theory is the Correspondence theory, which is the theory of truth which argues that a statement is true if it corresponds to the facts or objects described by the statement. This theory is adhered to by followers of realism. The second theory, Coherence theory, focuses on the suitability or consistency of a statement with other statements that are recognized as true. This theory measures truth based on the relationship between statements. The third theory of Pragmatism says that the truth of a statement is measured based on its usefulness in life practical.